Experimental Results of Electron Method for Remote Spacecraft Charge Sensing - M. T. Bengtson; K. T. Wilson; H. Schaub (Space Weather)
Abstract Remote charge sensing is a technique that can provide valuable insight into spacecraft‐environment interactions, as well as enable missions that leverage electrostatic interactions between multiple spacecraft or involve docking maneuvers in harsh charging environments. The concept discussed in this paper uses a co‐orbiting servicing spacecraft to measure the energies of secondary electrons or photoelectrons that are emitted from the target object with initial energies of a few electron volts. The electrons are accelerated toward the servicing spacecraft, which is at a known positive potential (relative to the target), where they are measured by an energy analyzer. Given the potential of the servicing spacecraft, the potential of the target can be accurately determined. Results are presented from experiments conducted in a vacuum chamber to investigate the touchless sensing concept. Specifically, the feasibility and accuracy of the electron method is considered for different materials, charge scenarios, and relative geometries. The results show that the surface potential of a flat plate can be accurately determined for a range of metallic surface materials, voltages, and relative angles.